An innovative submucosal filler for esophageal endoscopic submucosal dissection: A porcine model study (with video) - LiLin Lin; SuYu Chen; Rui Huang; Jianhua Chen; Juan Lin; Hong Shi (PLoS ONE, 2025)
Background Esophageal endoscopic submucosal dissection (ESD) a more challenging procedure. Numerous studies have explored submucosal injection materials from diverse perspectives. However, there is no consensus yet, and further exploration is still required. This study aimed to evaluate the efficacy of a novel submucosal filler, acetylcysteine, which is commonly used in respiratory medicine, when applied for the first time in ESD procedure of the porcine esophagus. Methods A self-controlled survival study was carried out on porcine model. In each pig, the novel submucosal filler was injected in one part of the esophagus (Experimental group; Group E), while normal saline was injected in another part (Control group; Group C) during the ESD procedure. Additionally, one pig received a submucosal injection of normal saline as a negative control to observe baseline daily movements and pathology following ESD. One month post- ESD, endoscopic and pathological evaluations were conducted to assess wound healing and other vital organs, allowing for a comprehensive assessment of the long – term impact and efficacy of the filler in this novel application context. Results The dissection time per unit area in Group E was notably shorter than in Group C (3.79 ± 1.38 minutes vs. 5.79 ± 1.22 minutes; P = 0.004). Group E also required a smaller volume of submucosal filler per unit area than Group C (3.48 ± 1.07 ml vs. 7.48 ± 3.96 ml; P = 0.039). However, There were no significant differences between Group E and Group C regarding the complication rate and thickness of the submucosal layer in the ESD specimens. Pathological evaluation of wound healing and other vital organs demonstrated comparable results in Group E and Group C. Conclusion This novel submucosal filler can expedite the ESD process without increasing the incidence of complications.